Designing Web-Based DISC Psychology Personality Analysis Tests - Daniel Aditama Somatdie; Erdhi Widyarto; Alb. Dwiyoga Widiantoro (SISFORMA, 2019)
Using a manual system in the companies or organizations today, has many disadvantages like inefficient, wasting time, require a lot of costs, and make work difficult. By integrating a DISC personality analytical psychological test with information system, the tests are carried out with computers initially using paper, so it more economical for using less paper. More than that, the test results are done automatically check by the computer, no need to manually check by the psychologist. In addition to being effective in examining, the validation of examinations is very high because it can recover human errors.